If it's not what You are looking for type in the equation solver your own equation and let us solve it.
v in (-oo:+oo)
(2-v)/2 = (3*v-2)/5 // - (3*v-2)/5
(2-v)/2-((3*v-2)/5) = 0
(2-v)/2+(-1*(3*v-2))/5 = 0
(5*(2-v))/(2*5)+(-1*2*(3*v-2))/(2*5) = 0
5*(2-v)-1*2*(3*v-2) = 0
14-11*v = 0
(14-11*v)/(2*5) = 0
(14-11*v)/(2*5) = 0 // * 2*5
14-11*v = 0
14-11*v = 0 // - 14
-11*v = -14 // : -11
v = -14/(-11)
v = 14/11
v = 14/11
| 1+(2p+1)=2p | | y=-2x+2graph | | (2-v)/2=((3v | | 2n=3.5-8 | | b(b-5)=24 | | jay=cut*e | | 111=1-2(1+8n) | | michel=cute | | 10(x^2+4x+4)=40(x+2) | | m/300=75/18 | | -10n-1=71 | | 175=-16t^2+100t | | 35+(-13)+(+8)-(-6)= | | (38-((x*7)+x))+((x*7)+x)=38 | | 54.5+10.5x= | | 764=4(x+19) | | 7a-3b+8a-5b= | | 10.5+54.5x= | | (x*x)+2x=120 | | 2x^2+9x-45=0 | | -12=2x+4 | | -8x+(-16)=24 | | 5p+7-5p=-7*(p-3) | | 5p+7-5p=7*(p-3) | | 3(3-1)=x | | 96.3=9(m+2.4) | | (4b+5)+(4b-2)= | | -2(3y-4)+6= | | 3(3-1)= | | y-2=-13 | | 7x-36=b | | 1/7x-y=18 |